2022
DOI: 10.3389/fpsyg.2022.995384
|View full text |Cite
|
Sign up to set email alerts
|

How attachment affects users’ continued use intention of tourism mobile platform: A user experience perspective

Abstract: Continued use intention of customers is a critical factor in the development of tourism mobile platforms (TMP), which reflects the degree of users’ attachment to the platforms. However, existing research in this field intends to investigate users’ attachment to a TMP by focusing on the overall cognitive satisfaction of the users, which deviates from the “cognition-affect” framework in psychology. Following the stimulus–organism–response (S-O-R) framework, this paper draws upon the attachment theory and the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Liu Dongmeng's research found that perceived interaction can positively affect emotional attachment through need fulfillment and self-extension [14] . He Yuting studied user behavior from the perspective of interactivity, and found that improving user perception control, responsiveness and entertainment can strengthen the audience's emotional attachment to the live broadcast platform [15] .Yinghaiyang found that interactive perception has a positive impact on platform attachment in the dimension of emotional attachment when studying users' intention to continue using paid knowledge platform [16] .Therefore, the following hypothesis is proposed: H1a: User control has a positive impact on platform identity H1b: Entertainment has a positive impact on platform identity H1c: Connectedness has a positive impact on platform identity H1d: Responsiveness has a positive impact on platform identity H2a: User control has a positive influence on platform affection H2b: Entertainment has a positive influence on platform affection H2c: Connectedness has a positive impact on platform affection H2d: Responsiveness has a positive effect on platform affection…”
Section: The Relationship Between Perceived Interaction and Emotional...mentioning
confidence: 99%
“…Liu Dongmeng's research found that perceived interaction can positively affect emotional attachment through need fulfillment and self-extension [14] . He Yuting studied user behavior from the perspective of interactivity, and found that improving user perception control, responsiveness and entertainment can strengthen the audience's emotional attachment to the live broadcast platform [15] .Yinghaiyang found that interactive perception has a positive impact on platform attachment in the dimension of emotional attachment when studying users' intention to continue using paid knowledge platform [16] .Therefore, the following hypothesis is proposed: H1a: User control has a positive impact on platform identity H1b: Entertainment has a positive impact on platform identity H1c: Connectedness has a positive impact on platform identity H1d: Responsiveness has a positive impact on platform identity H2a: User control has a positive influence on platform affection H2b: Entertainment has a positive influence on platform affection H2c: Connectedness has a positive impact on platform affection H2d: Responsiveness has a positive effect on platform affection…”
Section: The Relationship Between Perceived Interaction and Emotional...mentioning
confidence: 99%